Estudio de prefactibilidad para la instalación de una planta de producción de macerado de café (Coffea arabica) en pisco - Corpus Rodriguez, Johan Rusbel (2023)
The present project aims to demonstrate the technical, economic, financial, and market feasibility of a coffee maceration plant in Pisco, packaged in 500 ml bottles. By establishing a maceration plant, an innovative product would be launched into the market, offering something different for the preparation of cocktails and beverages during celebrations for the Peruvian consumer. Pisco was chosen as the base for the product, considering that it is the flagship beverage and is considered part of the identity of every Peruvian. An estimated demand of 121 505 bottles of macerated coffee is projected for the fifth year, targeting the socioeconomic levels A and B of the population residing in Metropolitan Lima, aged over 18, and who consume alcoholic beverages at various social events. The plant is in the district of Lurin, in the department of Lima, occupying an area of 450 m2, with an annual capacity of 181 479,05 bottles. The production process begins with the reception of Pisco and coffee beans, which are poured into hot maceration tanks, then filtered and bottled in 500 ml bottles. The total investment amount is S/. 1 779 129,52, with 60% financed through a loan from BBVA, and the remaining 40% being equity. The economic and financial evaluation revealed an opportunity cost of 17.90%, and the results are beneficial for the shareholders, with a Net Present Value (NPV) of S/. 1 185 731,52, an Internal Rate of Return (IRR) of 42.81%, a cost/benefit ratio of 1,67, and a payback period of 2,42 years.